Oil Refinery Heat Exchanger Network Cleaning Scheduling Strategy with Unit Cleanability Consideration - Hairul Huda; Renanto Handogo; Totok Ruki Biyanto; Wei Wu; Vincentius Surya Kurnia Adi (ASEAN Journal of Chemical Engineering, 2020)
Heat exchanger networks (HENs) play an important role in the chemical industries. Unfortunately, fouling is inevitable in heat exchangers operation. Therefore, the optimal cleaning procedure is required to restore heat exchangers' performance periodically. A systematic cleaning scheduling strategy for the heat exchanger network in an oil refinery is proposed in this work. There are 11 operating heat exchangers in an oil refinery to be reviewed. Different cleaning decision scenarios based on the overall heat transfer coefficient are explored for optimal cleaning schedule performance. The daily number of exchangers available to be cleaned i.e., the unit cleanability, is investigated while minimizing the energy consumption and the additional heat requirement due to the offline heat exchanger under cleaning procedure. The HEN performance and the energy-saving from the cleaning procedures are benchmarked with the uncleaned HEN. The results indicate that the cleaning procedure significantly increases the HEN performance and simultaneously reduces the heat requirement if compared to the untreated HEN benchmark. The possible conflicting situation is discussed when some heat exchangers are waiting to be cleaned due to the unit cleanability restriction, which allows the overall heat transfer coefficient to be below the allowed limit. Therefore, nonconflicting cleaning scheduling is also addressed in this work by relaxing the unit cleanability limit. Furthermore, the optimal cleaning schedule is also suggested for user reference. In this work, the optimum cleaning schedule with minimum energy consumption and maximum energy saving could be achieved when cleaning decision limit is set at 40% decrease of overall heat transfer coefficient. In the contrast, the lowest number of cleaning procedures is associated with 90% decrease in the overall heat transfer coefficient as the cleaning decision limit.